2022
DOI: 10.3389/fneur.2022.865714
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Intracranial Lymphatic Circulation and Its Involvement in Disorders

Abstract: The lymphatic system is an important part of the circulatory system, as an auxiliary system of the vein, which has the functions of immune defense, maintaining the stability of the internal environment, and regulating the pressure of the tissue. It has long been thought that there are no typical lymphatic vessels consisting of endothelial cells in the central nervous system (CNS). In recent years, studies have confirmed the presence of lymphatic vessels lined with endothelial cells in the meninges. The periven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 120 publications
(170 reference statements)
0
2
0
Order By: Relevance
“…WTAP has also been shown to be upregulated in AML cells and to play an essential role in the abnormal proliferation and inhibition of differentiation of leukemic cells ( 130 ). METTL14 was highly expressed in AML cells carrying t(11q23), t ( 15 , 17 ) or t(8;21) translocations and was downregulated during myeloid differentiation ( 131 ). Knockdown of METTL14 facilitated AML and normal HSPC cells’ myeloid terminal differentiation and suppressed the proliferation of AML cells.…”
Section: M6a Modification and Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…WTAP has also been shown to be upregulated in AML cells and to play an essential role in the abnormal proliferation and inhibition of differentiation of leukemic cells ( 130 ). METTL14 was highly expressed in AML cells carrying t(11q23), t ( 15 , 17 ) or t(8;21) translocations and was downregulated during myeloid differentiation ( 131 ). Knockdown of METTL14 facilitated AML and normal HSPC cells’ myeloid terminal differentiation and suppressed the proliferation of AML cells.…”
Section: M6a Modification and Solid Tumorsmentioning
confidence: 99%
“…Despite the use of comprehensive therapies such as surgery, radiotherapy, and novel immunotherapies, the 2-year survival rate for GBM is only 15 months, and reliable biomarkers and effective immunotherapy targets for GBM are still lacking ( 6 , 14 ). Patients with GBM present a complex state of immune dysfunction involving several mechanisms of immunosuppression and tolerance, and immunotherapy has emerged as a novel approach to GBM treatment ( 6 , 15 ). Studies have demonstrated that GBM is more heterogeneous than peripheral tumors, which indicates that several factors including RNA modification, tumor microenvironment (TME), and stem cell phenotype may influence immune checkpoint blockade therapy and developmental plasticity in GBM ( 16 ).…”
Section: Introductionmentioning
confidence: 99%